Novel Assay Assessment of Oxidative Stress Biomarkers in Patients with Keratoconus: Thiol–Disulfide Homeostasis. (2nd September 2017) - Gulpamuk, Bayram; Koç, Mustafa; Karatepe, Mustafa Salih; Yildiz, Aydan; Erel, Ozcan; Neselioglu, Salim; Yilmazbas, Pelin
ABSTRACT: Purpose : To investigate systemic oxidative stress by evaluating thiol–disulfide homeostasis using a novel automated homeostasis assay in keratoconus patients. Methods : Twenty-eight patients with keratoconus and 30 control subjects of a similar age and gender were enrolled in the present study. The native thiol, total thiol, and disulfide levels and the disulfide–native thiol, disulfide–total thiol, and native thiol–total thiol ratios were analyzed and compared between the keratoconus and control groups using a novel automatized spectrophotometric assay. Results : The median serum native thiol value was 441.5 (362.6–488.1) in the keratoconus group and 467.8 (401.8–564.6) in the control subjects. The median serum total thiol value was 467.9 (375–580.6) in the keratoconus group and 503.3 (437.7–578.5) in the control subjects. The median serum disulfide value was 20.1 (6.2–46.3) in the keratoconus patients and 16.7 (1.1–20.8) in the controls. There were significant differences between the native thiol, total thiol, and disulfide levels of the keratoconus patients and controls ( p = 0.001, p = 0.04, and p = 0.03, respectively) and the disulfide–native thiol, disulfide–total thiol, and native thiol–total thiol ratios of these two groups ( p = 0.02, p = 0.01, and p = 0.001, respectively). We found no significant correlation between age and any of the thiol–disulfide parameters ( p > 0.05 for all values). Conclusions : There is an imbalance in the systemic thiol–disulfide homeostasis in KC patients. This metabolic imbalance may play an important role in the pathogenesis of keratoconus; thus, it can be discussed in terms of the prevention, diagnosis, and the possible treatment for keratoconus.